Pengaruh keputusan investasi, keputusan pendanaan, dan kebijakan dividen terhadap nilai perusahaan yang terdaftar di Bursa Efek Indonesia - Patrisia, Dina; Linda, Muthia Roza; Yulianti, Ursa (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2019)
This study aims to analyze the effect of investment decisions, funding decisions, and dividend policy on the value of the company. This research is classified as causative research. The populations in this study are all Manufacturing companies listed on the Stock Exchange in 2012-2016. The sampling technique in this study is using purposive sampling technique with a total sample of 213 samples. The data used is secondary data. The data analysis method used is multiple regression. The results showed that investment decision variables affect the value of the company in a positive direction, funding decisions affect the value of the company in a negative direction, and dividend policy affects the value of the company with a positive direction on Manufacturing companies listed on the IDX. With this research, it is expected that researchers who can further conduct research related to factors that influence the value of the company whose impact is higher than what researchers have met. By using different proxy and data processing methods to produce more accurate data processingKeywords: Investment decisions; funding decisions; dividend policy; company value